Probióticos do gênero Bacillus em dietas para pós-larvas de tilápia do Nilo (Oreochromis niloticus) - Castro, Valdir Silva de (2020)
The objective of this research was to evaluate different levels of probiotic in diets for Nile tilapia post-larvae. 1,680 Nile tilapia post-larvae were housed, with an initial average weight of 0.05 ± 0.01g distributed in 24 aquariums of 110 L, with 70 fry each aquarium, in a completely randomized design with six treatments and four repetitions, considering aquariums as an experimental unit. During the experiment, water quality parameters were monitored daily using a portable multiparameter probe. Obtaining mean values of temperature 26.9 ± 0.5 ° C, oxygen 4.0 ± 0.7 mg / L, conductivity 170.1 ± 46.6 μS / cm, pH 7.2 ± 0.5 A basal diet containing the inclusion of probiotic levels of the genus Bacillus 4.0x 1012 UFC (control (0.0); 0.02; 0.04; 0.06; 0.08; 0.10) g / 100g of feed. At the end of the experiment, the parameters of zootechnical performance of the animals were evaluated, where there were no significant differences. Although the different levels of inclusion of probiotic of the genus Bacillus in the diet does not provide zootechnical performance of Nile tilapia, it is recommended the inclusion of 0.08g / kg of probiotic of the genus Bacillus as it improves the intestinal health of post-larvae of Nile tilapia.